Molecular and laser spectroscopy : advances and applications - Gupta, V. P., 1942- (Elsevier, 2018)
"Molecular and Laser Spectroscopy: Advances and Applications provides students and researchers with an up-to-date understanding of the fast-developing area of molecular and laser spectroscopy. Editor V.P. Gupta has brought together the eminent scientists on a selection of topics to develop a systematic approach, first covering basic principles needed to understand each cutting-edge technique and application. This book acts as a standard reference for advanced students of molecular and laser spectroscopy and as a graduate text for new entrants in the field. The book covers a wide range of applications of molecular and laser spectroscopy in diverse areas ranging from materials to medicine and defence, biomedical research, environmental monitoring, forensic investigations, food and agriculture, and chemical, pharmaceutical and petrochemical processes. Researchers and scientific personnel in these fields will learn the latest techniques in order to put them to practical use in their work. Covers several areas of spectroscopy research in a single volume, saving researchers timeIncludes exhaustive lists of research articles, reviews and books at the end of each chapter to point readers in the right direction for further learningFeatures illustrative examples of the varied applicationsServes as a practical guide to those interested in using molecular and laser spectroscopy tools in their research and field applications"--